Indoplatessa gen. nov.—a new monoraphid diatom genus based on Platessa arborea (Achnanthidiaceae, Bacillariophyceae) - Tseplik, Natalia; Radhakrishnan, Cheran; Karthick, Balasubramanian; Kulikovskiy, Maxim (Phytotaxa, 2025)
Indoplatessa, a new monoraphid diatom genus, is described based on a detailed morphological investigation using light and scanning electron microscopy analysis. The type species for this genus was previously described as Platessa arborea Radhakrishnan, Sherly & Karthick from tree bark moss habitat from Eastern Himalayas, India. This species differs from all other monoraphid genera by predominantly uniseriate striae on both valves, central raphe endings that are located in a rounded depression externally and distinctly hooked internally, slit-like areolae and internally thickened interstriae. The morphological resemblance was assessed in relation to all other Platessa species and compared with other monoraphid genera.